The Potential of Bacteriophage-Antibiotic Combination Therapy in Treating Infections with Multidrug-Resistant Bacteria - Abdul-Halim Osman; Fleischer C. N. Kotey; Alex Odoom; Samuel Darkwah; Raphael K. Yeboah; Nicholas T. K. D. Dayie; Eric S. Donkor (MDPI AG, 2023)
The growing threat of antibiotic resistance is a significant global health challenge that has intensified in recent years. The burden of antibiotic resistance on public health is augmented due to its multifaceted nature, as well as the slow-paced and limited development of new antibiotics. The threat posed by resistance is now existential in phage therapy, which had long been touted as a promising replacement for antibiotics. Consequently, it is imperative to explore the potential of combination therapies involving antibiotics and phages as a feasible alternative for treating infections with multidrug-resistant bacteria. Although either bacteriophage or antibiotics can potentially treat bacterial infections, they are each fraught with resistance. Combination therapies, however, yielded positive outcomes in most cases; nonetheless, a few combinations did not show any benefit. Combination therapies comprising the synergistic activity of phages and antibiotics and combinations of phages with other treatments such as probiotics hold promise in the treatment of drug-resistant bacterial infections.